Learning To Speak English Through Hellotalk Applicationl Narrative Inquiry Research - Lisa Dwy Puspita; Mansyur Srisudarso; Totoh Tauhidin (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study focuses on the effectiveness of Mobile-Assisted Language Learning (MALL) through the HelloTalk application in improving students' English speaking skills. It presents the findings of a classroom action research conducted in three cycles with computer science students at Pamulang University. The research demonstrates that HelloTalk positively impacts students' confidence, motivation, pronunciation, grammar, vocabulary, fluency, and comprehension in speaking English. While emotional challenges may arise, the study emphasizes the importance of a supportive learning environment provided by teachers and language exchange partners. Additionally, it highlights the cognitive benefits of HelloTalk, including vocabulary acquisition, improved grammar understanding, enhanced listening skills, comprehension of idiomatic expressions, and cultural insights. Overall, the research underscores the effectiveness of HelloTalk as a tool for immersive and interactive language learning, while emphasizing the significance of a supportive environment to address emotional barriers.